Meningkatkan Hasil Belajar Siswa Pada Tema “Indahnya Keberagaman Di Negeriku” Melalui Pendekatan Kontekstual Di Kelas IV: Improving Student Learning Outcomes on the Theme of “The Beauty of Diversity in My Country” Through a Contextual Approach in Grade IV - Faizal Faizal; Muhammad Aqil; Nurul Fitriah Aras; Surahman Surahman (Institut Agama Islam Daruttaqwa Gresik, 2025)
through two cycles, each cycle consisting of four stages (a). Planning (b). Implementation of Action (c). Observation and (d). Reflection. The study has an important objective in improving student learning outcomes on the theme